Using store-forward technique to conserve energy in wireless sensor networks: initial step for routing mechanism - Ahmedy, Ismail (AICIT, 2012)

(untitled)
Wireless sensor network (WSN) is a technology which consists a number of sensor nodes distributed among of an area usually for monitoring purposes. As the emerging of this technology has been rapidly increased nowadays, the successful of the wireless sensor networks application is highly depends on the reliable communication among the sensor nodes. One major problem in wireless sensor networks environment is the limitation of the physical resource in sensor nodes which energy resource has been identified as a critical constraint for achieving the demanding capabilities in wireless sensor networks application. Packet dissemination is one of the data transmission method in wireless sensor networks routing protocol where it would cause high energy consumption in sensor node due to the high energy consuming for disseminate the packet through the network. Initial step in routing protocol using packet dissemination method for wireless sensor networks could contribute energy efficiency if it has the ability to reduce the energy consumption. The proposed store-forward technique is to define the initial step in packet dissemination routing protocol whereas to identify the neighbor nodes without consuming high energy in sensor nodes. The result shows using the store-forward technique gave significant impact in conserving the energy in sensor nodes where it slightly reduce the energy consumption in terms of power availability after the routing initialization process is executed.